2016
DOI: 10.1155/2016/7842340
|View full text |Cite
|
Sign up to set email alerts
|

Stachytarpheta jamaicensis (L.) Vahl: From Traditional Usage to Pharmacological Evidence

Abstract: Introduction. Stachytarpheta jamaicensis (L.) Vahl belongs to the family of Verbenaceae and is commonly known as Gervao, Brazilian tea, verbena cimarrona, rooter comb, or blue porter weed. It is one of the important plants with high medicinal and nutraceutical benefits. S. jamaicensis contains various medicinal properties in traditional and folk medicinal systems, with cures for several diseases. Objective. The objective of this review paper is to collect information concerning the morphology, distribution, tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 31 publications
(47 reference statements)
1
25
0
5
Order By: Relevance
“…Carbohydrates, alkaloids, saponins, phenolic compounds, and flavonoids were present in the powdered sample. The presence of these phytochemicals agrees with the earlier report of Liew and Yong, 19 who identified additional phytochemicals like terpenoids, steroids, proteins and glycosides in the leaves of S. jamaicensis. Figure 1 represents the percentage free radical scavenging activity of the methanol and ethyl acetate extracts of S. jamaicensis leaves.…”
Section: Phytochemical Constituents Of Stachytarpheta Jamaicensis Leavessupporting
confidence: 91%
“…Carbohydrates, alkaloids, saponins, phenolic compounds, and flavonoids were present in the powdered sample. The presence of these phytochemicals agrees with the earlier report of Liew and Yong, 19 who identified additional phytochemicals like terpenoids, steroids, proteins and glycosides in the leaves of S. jamaicensis. Figure 1 represents the percentage free radical scavenging activity of the methanol and ethyl acetate extracts of S. jamaicensis leaves.…”
Section: Phytochemical Constituents Of Stachytarpheta Jamaicensis Leavessupporting
confidence: 91%
“…S. jamaicensis has been reported to contain secondary metabolites alkaloids, flavonoids, phenols, steroids, and terpenoids; and has traditionally been used for medicinal purpose in various countries (Putera and Shazura 2010). The active compounds have pharmacological effects as antacid, analgesic, anti-inflammatory, hypotensive, antihelminthic, diuretic, laxative, lactagogue, purgative, sedative, spasmogenic, vasodilator, vulnerary, and vermifuge properties (Liew and Yong 2016). Our study showed that the polyisoprenoid of S. jamaicensis had moderate inhibitory effects on the growth of E. coli and S. aureus.…”
Section: Resultsmentioning
confidence: 61%
“…Plant-derived medicines have been part of traditional healthcare in most parts of the world for thousands of years. As such, there is increasing interest in ethnobotany for the subsequent isolation and identification of novel therapeutic agents to help stem the high prevalence of hospital-acquired and community-acquired bacterial infections (Chariandy et al 1999;Palombo and Semple 2001;Liew and Yong 2016). Further, given the increasing incidence of antibiotic resistance (Monroe and Polk 2003), there is a continual need for new and effective bactericidal agents (Palombo and Semple 2001).…”
Section: Antimicrobial Activitymentioning
confidence: 99%